2015
DOI: 10.1038/nature14561
|View full text |Cite
|
Sign up to set email alerts
|

Competitive binding of antagonistic peptides fine-tunes stomatal patterning

Abstract: During development, cells interpret complex, often conflicting signals to make optimal decisions. Plant stomata, the cellular interface between a plant and the atmosphere, develop according to positional cues including a family of secreted peptides, EPIDERMAL PATTERNING FACTORS (EPFs). How these signaling peptides orchestrate pattern formation at a molecular level remains unclear. Here we report that Stomagen/EPF-LIKE9 peptide, which promotes stomatal development, requires ERECTA (ER)-family receptor kinases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
244
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(254 citation statements)
references
References 33 publications
9
244
0
1
Order By: Relevance
“…Both ER/ERLs and SERK1/SERK2/ SERK3/SERK4 are required for stomatal patterning (Shpak et al, 2005;Meng et al, 2015). EPF (EPIDERMAL PATTERNING FACTOR) small proteins trigger the interaction of ER/ERL with SERK1 to SERK4, while the TOO MANY MOUTHS-SERK association is independent on EPFs (Lee et al, 2015;Meng et al, 2015). Loss-of-function mutants of SERK1 to SERK4 genes exhibit the same phenotype in floral organ abscission as that of hae hsl2 and ida (inflorescence deficient in abscission) mutants (Butenko et al, 2003;Cho et al, 2008;Meng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Both ER/ERLs and SERK1/SERK2/ SERK3/SERK4 are required for stomatal patterning (Shpak et al, 2005;Meng et al, 2015). EPF (EPIDERMAL PATTERNING FACTOR) small proteins trigger the interaction of ER/ERL with SERK1 to SERK4, while the TOO MANY MOUTHS-SERK association is independent on EPFs (Lee et al, 2015;Meng et al, 2015). Loss-of-function mutants of SERK1 to SERK4 genes exhibit the same phenotype in floral organ abscission as that of hae hsl2 and ida (inflorescence deficient in abscission) mutants (Butenko et al, 2003;Cho et al, 2008;Meng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, A N data also are correlated directly with iWUE values calculated in the same plants. We also evaluated the same plants for the expression of the tomato genes homologous to those involved in the regulation of stomatal development in Arabidopsis: LeEPFL9, also known as STOMAGEN (Sugano et al, 2010), and genes encoding EPF1 and EPF2, two intercellular signaling factors that function as antagonists of LeEPFL9, since they act as negative regulators of stomatal development (Lee et al, 2015).…”
Section: Stomatal Density and Expression Of Genes Involved In Stomatamentioning
confidence: 99%
“…Polyploid plants often have negative relationships between stomata size and stomata density (Khazaei et al 2010;Miller et al 2012), and the regulation mechanisms between stomata size and stomata density are not known yet. Recent study indicated that stomata density was controlled by stomagen in Arabidopsis (Lee et al 2015). Increased numbers of chromosomes in polyploids often changes a lot of gene expressions, resulting in phenotypic alteration including stomata density in plant (Comai 2005).…”
mentioning
confidence: 99%